THE SOLVABILITY OF BOUNDED LINEAR OPERATOR EQUATION WITH NON-INVERTIBLE OPERATORS - Muhsin, Salim Dawood (MAGISTRA, 2014)
In this paper, we give the necessary and sufficient conditions for get general solutions of bounded operator equation CBXAAXB ï½ï« (1) , where A and B are non-invertible operator .on complex Hilbert space H and properties of the mapping BXAAXB